Frequency and Antimicrobial Resistance Patterns of Bacterial Species Isolated from the Body Surface of the Housefly (Musca domestica) in Akure, Ondo State, Nigeria - Babatunde Odetoyin; Babatunde Adeola; Olarinde Olaniran (Tehran University of Medical Sciences, 2019)
Background: The emergence and spread of antibiotic resistant bacteria has become a serious problem worldwide. Houseflies are potential carriers of pathogenic and resistant bacteria and could be contributing to the global spread of these strains in the environments.We investigated the prevalence and antimicrobial resistant profiles of bacteria isolated from houseflies in Akure. Methods: Twenty-five houseflies were captured by a sterile nylon net from the slaughterhouse, garbage dump, human house, hospital, and eatery from 9:00am to 1:00pm when the flies were active and transported immediately to the laboratory in sterile containers for processing. Bacterial loads were enumerated by serial dilution and plating on nutrient agar and selective media. Bacteria species were isolated by conventional isolation technique. Antibiotic susceptibility test was determined by the Kirby-Bauer disc diffusion technique. Results: Sixty-seven bacterial species were isolated from 25 samples that were collected. The predominant bacterial species was Escherichia coli (n= 31, 45%), followed by Klebsiella pneumoniae (n= 17, 25%), Staphylococcus aureus (n= 11, 16%) and Pseudomonas aeruginosa (n= 3, 4.3%). The bacterial load of the samples ranged from 9.7×105CFU/mL to 1.65×106CFU/mL. The results revealed that all isolates of Pseudomonas aeruginosa, Salmonella spp, and Proteus mirabilis were resistant to streptomycin and cotrimoxazole, augmentin and amoxicillin respectively. None of the S. aureus isolates was resistant to cotrimoxazole, chloramphenicol, sparfloxacin, augmentin, and ofloxacin. All isolates were multi-drug resistant. Conclusion: House flies that were collected from the slaughterhouse, garbage dump, human house, hospital, and eatery may participate in the dispersal of pathogenic and resistant bacteria in the study environment.